Human rights discourse and memories of the recent past in the anti-trafficking campaign in Argentina (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The aim of this paper is to address the singular configuration of the Argentinian anti – trafficking campaign during the 2008-2015 period. Bearing in mind that the campaign’s discourse was originally developed in transnational and supranational spaces, I am interested in analyzing the vernacularization processes through which the campaign was recreated in the local context. I suggest that the singularity of the Argentinean anti-trafficking campaign is its appeal to a set of political rethorics from human rights’ organizations in their historical demands of “memory, truth and justice”. Finally, I present some reflections on the feminist uses of human rights discourses, seeking to grasp their potentialities, limits and ambivalences.
Keywords: anti-trafficking campaign, human rights, prostitution, feminisms